The efficiency of polyaluminum chloride and anionic polyacrylamide in removing the hot rolling steel factory effluent turbidity - Habibi, M.; Mobarakeh, M. N.; Chamani, A.; Abdullah, Luqman Chuah; Zamani-Ahmadmahmoodi, R. (Institute for Ionics, 2024)
The coagulation and flocculation method stands out as a widely utilized approach in industrial wastewater treatment. This study explores the application of a new sedimentation concept, focusing on one-step removal, and evaluates the effectiveness of polyaluminum chloride (PAC) and anionic polyacrylamide (PAM) in reducing turbidity in simulated hot-rolled steel factory effluent. The investigation considers various independent variables such as pH, stirring time, temperature, and concentrations of oil and suspended solids. The response surface method (RSM) is employed for a more precise examination of these parameters. Results indicate that increasing PAC dosage to 5 mg/L enhances turbidity removal efficiency, meeting the water turbidity standard of less than 20 NTU for the rolling process. Conversely, the highest efficiency with polyacrylamide occurs at a lower concentration (0.1 mg/L), with efficiency decreasing as PAM amounts rise, hindering coagulation and flocculation processes. Despite polyacrylamide’s higher consumption efficiency, the study suggests that PAC exhibits superior wastewater turbidity removal at optimal concentrations. Overall, this research introduces a novel one-step treatment method for rolling mill effluent, streamlining the process, reducing energy consumption, and lowering treatment costs as compared to traditional methods.